Structural basis for the recognition of complex-type N-glycans by Endoglycosidase S - Beatriz Trastoy (Nature Portfolio, 2018)
Endoglycosidase S only recognizes one particular type of glycan within IgG antibodies but the molecular basis for this high specificity is not fully understood. Here, the authors present the crystal structure of product-bound Endoglycosidase S, revealing the determinants for its glycan specificity.